Person Perception in Young Children Across Two Cultures. Issue 3 (26th May 2016) - Chen, Eva E.; Corriveau, Kathleen H.; Harris, Paul L.
Abstract : To adult humans, the task of forming an impression of another social being seems effortless and even obligatory. In 2 experiments, we offer the first systematic cross-cultural examination of impression formation in European American and East Asian preschool children. Children across both cultures easily inferred basic personality traits, such as nice and mean, about unfamiliar peers from behavioral information, whether or not they were specifically prompted to do so. Children were able to identify peers they had seen before, to remember the traits associated with these peers, and to anticipate future behaviors consistent with the traits they had attributed. Thus, for basic traits, the ability to make behavior-to-behavior predictions, via an intervening trait inference, is present in young children across diverse cultures.